Studi Deskriptif Kuantitatif : Psychological Well-being pada Mantan Pecandu Narkoba yang Mantan Narapidana - Puput Nofia Rahma; Rida Yanna Primanita (Pusat riset dan Inovasi Nasional, 2025)
This research aims to look at Psychological Well-being in former drug addicts who are also ex-convicts. The population used was former drug addicts who were also former prisoners in Bukittinggi with 5 samples. This research uses non-parametric statistics with descriptive methods. The instrument used is an adaptation with a total of 36 items with aspects including a). Self Acceptance, b). Positive Relationship With Others, c). Autonomy d). Environmental Mastery, e). Purpoe In Life and f). Personal Growth. Based on the results of research that has been carried out, the Psychological Well-being results for the subject are in the Fair category with a percentage of 20%, High with a percentage of 60% and Very high with a percentage of 20%.